State Investment in Higher Education: Effects on Human Capital Formation, Student Debt, and Long-Term Financial Outcomes of Students - Rajashri Chakrabarti; Nicole Gorton; Michael F. Lovenheim (Center for Economic Studies and Ifo Institute (CESifo), 2020)
Most public colleges and universities rely heavily on state financial support. As state budgets have tightened in recent decades, appropriations for higher education have declined substantially. Despite concerns expressed by policymakers and scholars that the declines in state support have reduced the return to education investment for public sector students, little evidence exists that can identify the causal effect of these funds on long-run outcomes. We present the first such analysis in the literature using new data that leverages the merger of two rich datasets: consumer credit records from the New York Fed's Consumer Credit Panel (CCP) sourced from Equifax and administrative college enrollment and attainment data from the National Student Clearinghouse. We overcome identification concerns related to the endogeneity of state appropriation variation using an instrument that interacts the baseline share of total revenue that comes from state appropriations at each public institution with yearly variation in state-level appropriations. For four-year students, we find that state appropriation increases lead to lower student debt originations and a shorter time to degree. In the two-year sector, state appropriation increases lead to more collegiate and post-collegiate educational attainment, more educational debt consistent with the increased educational attainment but lower likelihood of delinquency and default, higher car and home ownerships, increases in their credit scores and improvement in the affluence of the neighborhood in which they live. Examining mechanisms, we find state appropriations are passed on to students in the form of lower tuition in the four-year sector, while for community colleges, we find evidence of both price and quality mechanisms, the latter captured in higher educational resources in key spending categories.
Keywords: I20; H72; H75; 330; postsecondary education; state appropriations; student loans; returns to education